Investigation into surface plasmon resonance based optical sensor - Leong, Joseph Jun Yih (2019)
This project seeks to use simple and inexpensive materials and methods to fabricate a micro-fluidic unit for the purpose of developing a lab-on-chip optical biosensor. The biosensor uses the principle of grating-coupled Surface Plasmon Resonance (SPR) to detect the change in concentration of sucrose solution. The experimental data from the SPR response can be used to validate and evaluate the performance of the microfluidic unit by observing the shift in the SPR curves. The micro-fluidic unit is created from the curing of Polydimethylsiloxane (PDMS) and then tested with a gold diffraction grating film on silicon wafer, which is created using interference lithography process. Preliminary results indicate that the mould type, size of micro-fluidic channel and design of the unit greatly affect its performance. Experiments involving the testing of the micro-fluidic units were performed over using a broadband white light, beam-splitter, polarizer and spectrometer, which was connected to the PC. The signal response was then evaluated using Ocean view software.